Lack of adipose-specific hexose-6-phosphate dehydrogenase causes inactivation of adipose glucocorticoids and improves metabolic phenotype in mice. (8th November 2019) - Wang, Jian; Wang, Ying; Liu, Limei; Lutfy, Kabirullah; Friedman, Theodore C.; Liu, Ya; Jiang, Meisheng; Liu, Yanjun
Abstract: Excessive glucocorticoid (GC) production in adipose tissue promotes the development of visceral obesity and metabolic syndrome (MS). 11β-hydroxysteroid dehydrogenase type 1 (11β-HSD1) is critical for controlling intracellular GC production, and this process is tightly regulated by hexose-6-phosphate dehydrogenase (H6PDH). To better understand the integrated molecular physiological effects of adipose H6PDH, we created a tissue-specific knockout of the H6PDH gene mouse model in adipocytes (adipocyte-specific conditional knockout of H6PDH (H6PDH AcKO ) mice). H6PDH AcKO mice exhibited almost complete absence of H6PDH expression and decreased intra-adipose corticosterone production with a reduction in 11β-HSD1 activity in adipose tissue. These mice also had decreased abdominal fat mass, which was paralleled by decreased adipose lipogenic acetyl-CoA carboxylase (ACC) and ATP-citrate lyase (ACL) gene expression and reduction in their transcription factor C/EBPα mRNA levels. Moreover, H6PDH AcKO mice also had reduced fasting blood glucose levels, increased glucose tolerance, and increased insulin sensitivity. In addition, plasma free fatty acid (FFA) levels were decreased with a concomitant decrease in the expression of lipase adipose triglyceride lipase (ATGL) and hormone-sensitive lipase (HSL) in adipose tissue. These results indicate that inactivation of adipocyte H6PDH expression is sufficient to cause intra-adipose GC inactivation that leads to a favorable pattern of metabolic phenotypes. These data suggest that H6PDH AcKO mice may provide a good model for studying the potential contributions of fat-specific H6PDH inhibition to improve the metabolic phenotype in vivo . Our study suggests that suppression or inactivation of H6PDH expression in adipocytes could be an effective intervention for treating obesity and diabetes.